Critical Political Economy approach to Global Political Economy - Navarrete M (Al-Qanṭara, 2022)
Abstract Critical Political Economy is a transdisciplinary field of enquiry that is gaining ever more popularity among scholars and activists alike. In addition to analysing social power relations that revolve around how humans collectively organise production and social reproduction over time and space, Critical Political Economy also problematises the resulting social inequalities and asymmetrical manifestations in private and public (state-)institutional settings. Particularly the various forms of exploitation that are constitutive to the continuation of global capitalism are brought into question rather than accepted as givens. Critical Political Economy not only offers a particular way of understanding the world, but also seeks to produce knowledge that allows for social emancipation and that ultimately contributes to the politicisation and the resilience of social struggles. Thus, while giving ontological primacy to the negative, Critical Political Economy is essentially committed to a positive ontology by animatingand awakening radical imagination about alternative futures.